Two Tunes, One Dance: Keeping Programming Agile - Learning Lab (USAID Learning Lab, 2017)

World Development Report 2017: Governance and the Law - World Bank (The World Bank, 2017)

Thinking and Working Politically – Are We Seeing the Emergence of a Second Orthodoxy? - Teskey, Graham (Abt Associates, 2017)
There now is a persuasive volume of evidence that demonstrates that capacity and technical knowledge alone are insufficient to change deeply entrenched political interests and bureaucratic norms. These critiques demonstrate that an understanding of power asymmetries is frequently the critical missing ingredient in project design and implementation. Many eminent thinkers have looked at the difference between success and failure in development, and all point to the primacy of domestic politics. This point has not been lost on development agencies and some have tried to provoke greater attention to the role that politics plays. However, this recognition is yet to pass into the mainstream of development practice. Despite the slow but sure accretion of this knowledge the international community seems to be wedded to doing development traditionally. The purpose of this paper is to consider the extent to which a ‘second orthodoxy’ is slowly emerging which can stand alongside, and in some cases may supplant, the ‘first orthodoxy’ of the traditional project framework. Care has to be taken in making this argument, as there is certainly no consensus within the development community on its importance, and even among advocates, there are slightly differing interpretations of what this second orthodoxy looks like. Further, it is not absolutely clear that the two orthodoxies can co-exist. The paper does not call for any ‘paradigm shift’ in how development practitioners conceptualise programs and projects, nor does it demand that the project framework be scrapped; the former would be impossible and the latter undesirable. Equally readers will find no claims that Doing Development Differently or ‘Thinking and Working Politically’ will always and everywhere guarantee better development outcomes. Rather, the paper seeks to summarise how the two orthodoxies differ, where the second orthodoxy now stands, and propose how it can be taken forward in practical terms.